INOVASI PEMBELAJARAN AL-QUR’AN PADA SISWA TINGKAT MENENGAH: ANALISIS FORMULASI DAN STRATEGI PEMAHAMAN MAKNA KANDUNGAN AYAT - Siregar, Rahmyani; Sitorus, Lufitasari; Mahrani, Nana (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
Learning the Qur'an tends to be based on linguistics and reading procedures, whereas at the intermediate level, students are also required to be able to understand the content of the A-Qur'an verse, with regard to this, of course, Islamic religious education teachers must be able to innovate learning so that the intended objectives can be achieved. With regard to this, this study aims to analyse the innovation of Qur'anic learning at secondary level students with a focus on the formulation of learning materials and strategies that have been implemented at SMK Tritech Informatika Medan. The research method used is qualitative, based on descriptive study. Data collection through observation, interview and documentation study. The results of the study explain that this research shows that innovations in learning materials and strategies at SMK Tritech Informatika Medan, which are supported by educational theories such as Social Constructivism and Multimedia Cognition, have succeeded in improving the quality and understanding of students of Qur'anic verses. The use of project-based methods and portfolio evaluation proved the effectiveness of this model. The findings emphasise the importance of tailoring learning methods to students' local needs, and are expected to be a reference for other educational institutions to achieve better learning outcomes.